The study of Sangiovese and Syrah varietal wines quality - Цыганкова, Елена Викторовна; Билько, Марина Владимировна (Technology audit and production reserves, 2015)
This article presents the results of studies of rose and red table wines from dry grapes Sangiovese and Syrah produced in Argentina, Greece, Israel, Spain, Italy and Chile. It is conducted a comparative analysis of organoleptic evaluation, physical and chemical characteristics, biological value at phenolic complex, the redox state of the wines produced in Ukraine from these grapes. It is shown that wine materials produced from grapes cultivated in the conditions of Ukraine are not inferior to foreign models according the organoleptic characteristics of wines from these grapes, and they also have a biological value and oxidation resistance. It is proved that for the production of red wines of high biological value from the grapes Sangiovese and Syrah the grapes must be processed with the intensification of must and pulp contact.